KEPEMIMPINAN KETUA PROGRAM STUDI DI MATA DOSEN - Wahyudi Wahyudi; Liana Dwi Septiningrum (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The leader is an organizational figure who is attached to a high position and authority, so that he has a greater ability to run the organization. The importance of the leadership position, so he becomes a strategic partner for all interests, both bottom and top streams, so that a leader needs to put himself in the interests of objective (precision). In essence, this research was conducted to see how the responses/perceptions/assessments of the lecturers on the leadership of the head of the study program from various aspects objectively, thus knowing a comprehensive contextual understanding of his leadership. This research was conducted at Pamulang University in the Postgraduate Program and the Faculty of Economics and Business, and the research correspondents were level one lecturers (study program developers). The sampling technique uses simple random and is carried out directly through the distribution of questionnaires. The research data were analyzed by descriptive quantitative method. The results of the study explain that the leadership of the head of the study program in the Postgraduate Program and the Faculty of Economics and Business has democratic characteristics. This is evidenced by the involvement of level one lecturers in all study program activities, both developmental and other activities.